Evaluación del uso de resinas como tratamientos de consolidación de arena in situ mediante pruebas de laboratorio con datos de un campo petrolero en Colombia (2023)
This work is carried out in conjunction with the company Halliburton Latin America SRL Sucursal Colombia, who requires the analysis of a resin by activation through pH as an in situ sand consolidation treatment, for which laboratory tests are carried out with sand from an oil field drilled in Colombia and with a high percentage of fines. To carry out the resin analysis, the porous volume of the reinforced core is established in the brass cell with screen 40 at the top, followed by sand 20/40, sand with a high percentage of fines that simulates formation, sand 40/60 and screen 80. Subsequently, brine is pumped with surfactant, resin treatment, acid activator, according to the porous volumes previously established by the laboratory. In this way, the treatment and its effectiveness are evaluated by taking samples at different flow rates and measuring their turbidity and permeability. After validating the method and confirming that there is no production of fines once the resin treatment is applied, the procedure is performed again, but with a sample of formation sand from an oil well in Colombia. However, this treatment will not be implemented in wells and once these aspects are determined, the technical-economic benefits offered by this consolidation treatment are evaluated.